Pengaruh Pengawasan Perusahaan Terhadap Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Sella Auni Aprilia; Fatmasari Sukesti; Mohammad Ridwan (Faculty of Economics and Business, Universitas Warmadewa, 2025)
This research is entitled The Effect of Company Supervision on Company Financial Performance. Case Study of Banking Companies Listed on the Indonesian Stock Exchange 2020-2023. The aim of this research is to analyze the simultaneous and partial influence of company supervisors on the financial performance of banking companies listed on the Indonesian stock exchange in 2020-2023. The data collection method used in this research is the documentation method with multiple linear regression analysis. Based on the research results, it shows that the variables board of commissioners, board of directors, audit committee and institutional ownership simultaneously influence the financial performance of banks listed on the Indonesian stock exchange in 2020-2023. The partial effect shows that the institutional ownership and managerial ownership variables have a positive effect on financial performance, while the board of commissioners, audit committee and board of directors have no effect on the financial performance of banking companies listed on the Indonesian stock exchange in 2020-2023.